Modulation of Amyloidogenesis Controlled by the C-Terminal Domain of Islet Amyloid Polypeptide Shows New Functions on Hepatocyte Cholesterol Metabolism - Pulido-Capiz, Angel; Díaz-Molina, Raúl; Martínez-Navarro, Israel; Guevara-Olaya, Lizbeth A.; Casanueva-Pérez, Enrique; Mas-Oliva, Jaime; Rivero, Ignacio A.; García-González, Victor (Frontiers in Endocrinology, 2018)
The islet amyloid polypeptide (IAPP) or amylin maintains a key role in metabolism. This 37-residues-peptide could form pancreatic amyloids, which are a characteristic feature of diabetes mellitus type 2. However, some species do not form amyloid fibril structures. By employing a biomimetic approach, we generated an extensive panel of optimized sequences of IAPP, which could drastically reduce aggregation propensity. A structural and cellular characterization analysis was performed on the C-terminal domain with the highest aggregation propensity. This allowed the observation of an aggregative phenomenon dependent of the lipid environment. Evaluation of the new F23R variant demonstrated inhibition of β-sheet structure and, therefore, amyloid formation on the native C-terminal, phenomenon that was associated with functional optimization in calcium and cholesterol management coupled with the optimization of insulin secretion by beta cells. When F23R variant was evaluated in microglia cells, a model of amyloidosis, cytotoxic conditions were not registered. In addition, it was found that C-terminal sequences of IAPP could modulate cholesterol metabolism in hepatocytes through regulation of SREBP-2, apoA-1, ABCA1, and LDLR, mechanism that may represent a new function of IAPP on the metabolism of cholesterol, increasing the LDL endocytosis in hepatocytes. Optimized sequences with only one residue modification in the C-terminal core aggregation could diminish β-sheet formation and represent a novel strategy adaptable to other pharmacological targets. Our data suggest a new IAPP function associated with rearrangements on metabolism of cholesterol in hepatocytes.